2020
DOI: 10.3390/ijerph17238930
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Education Level and Excessive Recreational Screen Time in Children: A Mediation Analysis

Abstract: There is increasing recognition of the adverse health consequences of excessive recreational screen time (RST) in children and adolescents. Early interventions that aim to reduce RST are crucial, but there are some controversies about which individual and parental variables affect RST in children. The aim of this study was to determine the relationship of parental education level with RST in children and early adolescents and to identify mediators of these relationships. This cross-sectional study examined a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 52 publications
4
15
0
1
Order By: Relevance
“…This association is consistent with what is reported in the scientific literature [37,49,50]. Estimated screen time is greater among adolescents than children, which is also in line with what has been noted in other studies [25,51].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This association is consistent with what is reported in the scientific literature [37,49,50]. Estimated screen time is greater among adolescents than children, which is also in line with what has been noted in other studies [25,51].…”
Section: Discussionsupporting
confidence: 93%
“…A work by Abdel Magid et al showed that among adolescents in the United States of America, screen time was higher in those whose parents had a low level of education [61]. Our results are also in line with a study by Pons et al which indicated that a high education level among mothers is associated with lesser screen time and other healthy habits [14,25]. The mechanism which underlies the association between a lower educational level and a greater amount of screen time is not entirely clear.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The study also found that children whose parents had college education levels spend more time on moderate-intensity activity than children whose parents had middle school education levels or below ( Wärnberg et al, 2021 ). The results of this study are also consistent with those of other studies ( Pons et al, 2020 ). So, the results of this study are not only limited to Chinese children but also consistent with those of Spanish and Caucasian children; the results showed that the educational level of the parents was related to the health habits of children ( Duch et al, 2013 ; Carson et al, 2017 ; Monserrat et al, 2020 ; Yañez et al, 2020 ).…”
Section: Discussionsupporting
confidence: 93%
“…Another factor with a potential effect on the health status of children and adolescents is the level of maternal education. Previous studies have identified positive associations between maternal education and several health events, such as reduced infant mortality [32], maintenance of exclusive breastfeeding [33], and less passive leisure time in front of screens [34]. Although there are factors that make it impossible to generalize the statement that the increase in maternal education level acts as a protective factor for health outcomes in the child and adolescent population, it is reasonable to believe that mothers with high educational levels can stimulate their children to develop autonomy and resist social and media pressures for an unhealthy aesthetic standard.…”
Section: Discussionmentioning
confidence: 99%